The Cambridge companion to American crime fiction - Nickerson, Catherine Ross (Cambridge University Press, 2010)
"From the execution sermons of the Colonial era to television programs like The Wire and The Sopranos, crime writing has played an important role in American culture. Its ability to register fear, desire and anxiety has made it a popular genre with a wide audience. These new essays, written for students as well as readers of crime fiction, demonstrate the very best in contemporary scholarship and challenge long-established notions of the development of the detective novel. Each chapter covers a sub-genre, from ?true crime? to hard-boiled novels, illustrating the ways in which ?popular? and ?high? literary genres influence and shape each other. With a chronology and guide to further reading, the Companion is a helpful guide for students of American literature and readers of crime fiction"--Provided by publisher.